Beyond Freedom and Oppression - Social Media, Refusal, and the Politics of Participation - Feldman, Zeena (AoIR Selected Papers of Internet Research, 2012)
This paper explores the relationship between social media, writing, and resistance. Drawing on a 2-year ethnographic study of the niche social network site CouchSurfing.org, I examine the dynamics and mechanisms of resistance that emerged within the site following CouchSurfings conversion from a non-profit to a for-profit structure. I focus specifically on three text-based tactics of resistance used by site members, and through the work of Patrick Hanafin and Maurice Blanchot, demonstrate how these tactics of refusal prompt a radical rethinking of refusal as such. Via the CouchSurfing case, I also argue that a proper appreciation of social medias political significance and the ideological stakes of being online requires attention to the conflictual relation between democracy, oppression, and capitalism. Finally, the paper reflects on the possibilities and limits of critique from within.